2014
DOI: 10.1002/dvdy.24218
|View full text |Cite
|
Sign up to set email alerts
|

Early divergence of central and peripheral neural retina precursors during vertebrate eye development

Abstract: During development of the vertebrate eye, optic tissue is progressively compartmentalized into functionally distinct tissues. From the central to the peripheral optic cup, the original optic neuroepithelial tissue compartmentalizes, forming retina, ciliary body and iris. The retina can be further sub-divided into peripheral and central compartments, where the central domain is specialized for higher visual acuity, having a higher ratio and density of cone photoreceptors in most species. Classically, models dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…Interestingly, astrocytes are known to be a heterogeneous cell population ( Bayraktar et al, 2015 ) and our data indicates that Angpt4 + astrocytes represent a specific subpopulation among the glial cells. Intriguingly, genetic deletion revealed that Angpt4 is especially important in the far peripheral segment that may develop via different pathway than central neural retina ( Venters et al, 2015 ). In addition, clinical wide-field fundus imaging has identified a number of vascular diseases in humans in the peripheral retina that can affect also macula even though primary defect is peripheral ( Bajwa et al, 2015 ; Wessel et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, astrocytes are known to be a heterogeneous cell population ( Bayraktar et al, 2015 ) and our data indicates that Angpt4 + astrocytes represent a specific subpopulation among the glial cells. Intriguingly, genetic deletion revealed that Angpt4 is especially important in the far peripheral segment that may develop via different pathway than central neural retina ( Venters et al, 2015 ). In addition, clinical wide-field fundus imaging has identified a number of vascular diseases in humans in the peripheral retina that can affect also macula even though primary defect is peripheral ( Bajwa et al, 2015 ; Wessel et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 48-hpf retina comprises the most diversity of RPCs because 48-hpf RPCs at the central region mostly undergo terminal cell divisions, whereas the ones at the peripheral region are still at the earlier stages of embryonic retinal development (He et al, 2012;Rapaport et al, 2004;Venters et al, 2015). Indeed, we were able to characterize seven distinct clusters from 48 hpf RPCs (Cluster 1 to Cluster 7-48 hpf; Fig.…”
Section: Defining Cellular Heterogeneity Of Embryonic Rpcsmentioning
confidence: 91%
“…Here, we applied BMP-beads at later stages of chick eye development. At the time of BMP5 application (E3.5/E4), the peripheral and the proximal RPE can be distinguished by the distribution of signalling components of the Wnt signalling pathway and MITF protein distribution (see also Venters et al, 2015 ). While Wnt2b transcripts are detected in the peripheral RPE, nuclear β-Catenin is detected in the proximal RPE ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8 A) ( Jasoni et al, 1999 ; Kubo et al, 2003 ; Kitamoto and Hyer, 2010 ). Thus, it is possible that BMP signalling in the presence of WNT2b might induce an RPE cell fate in the peripheral eye, whereas in the WNT2b-negative proximal RPE a conversion into NR is observed ( Figs 8 and 9 ) ( Venters et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%